Introduction: section 1: overview - Shanley, P.; Laird, S.A.; Pierce, A.R.; Guillen, A. (Routledge, 2002)
Certification is relatively new to forest policy tool that attempts to foster responsible resource stewardship through the labeling of consumer products. While many lessons can be drawn from timber certification, transfer of existing timber-based guidelines and procedures to NTFPs is inappropriate. Non-timber forest resources are a more difficult group of products to certify than timber due to a multitude of factors, including their exceedingly diverse and idiosyncratic nature and social and ecological complexity. However, in spite of these challenges, opportunities exist to promote sound ecological and social practices in NTFP management and trade through market tools such as certification, and their potential realization in practice is the subject of this manual.